Islamic intellectual capital and takaful financial performance - Nizar, Nadifa Salsabila; Falikhatun, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study examines the effect of Islamic intellectual capital that consists of Structural Capital, Human Capital, and Capital Employed on takaful financial performance in Southeast Asia and the Middle East during 2016- 2019. The dependent variable, takaful financial performance, is measured from the firm’s ROE. The independent variables in the current study are the Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE), and Audit Opinion used as a control variable. This study is a descriptive quantitative research using multiple linear regression analysis. The population of this study is the sharia insurance firms in Southeast Asia and Middle East countries with a total of 155 observations. This study shows that, two out of three variables are significant. Structural Capital Efficiency has a positive and significant effect, Capital Employed Efficiency has a negative and significant impact, and the Human Capital Efficiency has no significant effect on takaful financial performance. This study can be used as a reference, evaluation, and source of improvement for sharia insurance firms in optimizing the Islamic intellectual capital to improve the firm’s financial performance. To achieve this objective, companies could improve employees’ knowledge on sharia regulations, especially regarding sharia insurance, training, fulfilling employee’s rights, improving system quality, services, and transaction procedures.